Justice and Race in the Narrative of the American Slave and Toni Morrison's Favourite by Frederick Douglass - Garima, Anand (Journal of Social Science and Humanities, 2024)
This article is interested in justice and race in two African American novels: Frederick Douglass’s Narrative of the life of Frederick Douglass: an American slave and Toni Morrison's Beloved. Going from the quest of profit, we highlight the instrumentalization of the law by the Whites to the detriment of the black community. Violence is institutionalized and it causes many catastrophic consequences which destroy and disperse Negroes who are hardly exploited by the masters like Mr. Garner and Schoolteacher in Beloved, and Colonel Lloyd and Mr. Auld in Narrative of the life of Frederick Douglass: an American slave. Like in a capitalistic society, there is the class struggle opposing white masters to black slaves who represent the lower class or the proletarians. The relationships between the races have been endangered causing the death and the flight of many Negroes who run away from the place of their ill treatments or tortures. Because of the rudeness and cruelty of Schoolteacher, the Sweet Home men flee the plantation of Sweet Home, which engenders the loss of Sixo and the scattering of the family. In parallel, Douglass tells his flight from his master’s plantation with John and Freddy before he is caught and submitted to punishment. Douglass and Morrison emphasize the institutionalization of violence and the class struggle to appease the social climate prevailing in America by insisting on the moralization of human relationships.